2015
DOI: 10.1002/elan.201500046
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Determination of Hydroxylamine in the Presence of Thiosulfate in Water and Wastewater Samples Using a Nanostructure Modified Carbon Paste Electrode

Abstract: In this research, we report the preparation of a high sensitive voltammetric sensor for electrocatalytic determination of hydroxylamine (HX) in the presence of thiosulfate (TS). We describe the synthesis and characterization of CdO nanoparticles (CdO/NPs) with transmission electron microscopy (TEM) and X‐ray diffraction (XRD) methods. At an optimum condition, the two peaks are separated ca. 0.58 and 0.92 V for HX and TS at the surface of the proposed sensor. Square wave voltammetry (SWV) of HX exhibited two li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…On the other hand, BPOFc/BMPF6/NiO-SWCNTs/CPE exhibited an oxidation/reduction signal with ∆Ep = 130 mV that confirms quasi-reversible behavior of BPOFc/BMPF6/NiO-SWCNTs/CPE in the aqueous solution (curve a). The increasing oxidation signal of BPOFc/BMPF6/NiO-SWCNTs/CPE and simultaneous decrease in reduction signal of mediator after addition of 1.0 mM N-acetylcysteine, confirms an EC / interaction 59 , 60 between mediator and N-acetylcysteine on the surface of BPOFc/BMPF6/NiO-SWCNTs/CPE. The comparison of the electro-catalytic oxidation signal of N -acetylcysteine at the surface of BPOFc/BMPF6/NiO-SWCNTs/CPE with its signal at BPOFc/NiO-SWCNTs/CPE and BPOFc/BMPF6/CPE confirmed that the conductivity of electrode surface could be enhanced by the existence of NiO-SWCNTs and BMPF6.…”
Section: Resultsmentioning
confidence: 58%
“…On the other hand, BPOFc/BMPF6/NiO-SWCNTs/CPE exhibited an oxidation/reduction signal with ∆Ep = 130 mV that confirms quasi-reversible behavior of BPOFc/BMPF6/NiO-SWCNTs/CPE in the aqueous solution (curve a). The increasing oxidation signal of BPOFc/BMPF6/NiO-SWCNTs/CPE and simultaneous decrease in reduction signal of mediator after addition of 1.0 mM N-acetylcysteine, confirms an EC / interaction 59 , 60 between mediator and N-acetylcysteine on the surface of BPOFc/BMPF6/NiO-SWCNTs/CPE. The comparison of the electro-catalytic oxidation signal of N -acetylcysteine at the surface of BPOFc/BMPF6/NiO-SWCNTs/CPE with its signal at BPOFc/NiO-SWCNTs/CPE and BPOFc/BMPF6/CPE confirmed that the conductivity of electrode surface could be enhanced by the existence of NiO-SWCNTs and BMPF6.…”
Section: Resultsmentioning
confidence: 58%
“…With the advent of modified sensors and greater variability in the manufacture of electrochemical sensors, this technique has been introduced as a serious competitor for chromatographic methods in drug composition analysis [20][21][22][23][24][25][26][27][28][29][30]. The use of nanomaterial-modified sensors has been a major revolution in the design of sensitive sensors in recent years [31][32][33][34][35][36][37][38][39][40][41]. Nanomaterials with wide range application and new properties can be introduced as powerful catalysts in different industries such as electrochemical sensor filed [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…Determination of methyldopa in urine and blood sample in the presence of tyrosine isn't possible at a surface of bare electrodes using electrochemical methods. Application of modified electrodes as sensors can be help to trace analysis of electro-active compounds and resolve signal overlapping in simultaneous analysis [25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%